ENGLISH TEACHERS’ PERCEPTION ON ASSESMENT FOR LEARNING IN KURIKULUM MERDEKA - Heni Indrayani; NurDevi Bte Abdul; Ariana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out, what are teachers' perceptions of the use of Assessment for Learning in the Kurikulum Merdeka This research method is qualitative research with phenomena experienced by research subjects, such as behavior, perception, motivation, action, etc. Research data collected through interviews. This research was carried out at SMP Negeri 1 Kelara which used two teachers as subjects. The findings of this research indicate that the use of assessment for learning in the Kurikulum Merdeka it is difficult to ensure that teachers truly understand the concepts and apply them with the aim of improving learning rather than simply assessing outcomes. Because teachers have not seen the real results or effects of using this assessment, teachers sometimes face difficulties in directly assessing its success. In other words, although both approaches are expected to improve student learning, the difficulty in measuring their impact directly can make teachers feel uncertain about their effectiveness. This means that teachers must undergo more training so that teachers can understand and master well how to use it as/for assessment in learning.